PUCHI represses early meristem formation in developing lateral roots of Arabidopsis thaliana. (28th February 2022) - Bellande, Kevin; Trinh, Duy-Chi; Gonzalez, Anne-Alicia; Dubois, Emeric; Petitot, Anne-Sophie; Lucas, Mikaël; Champion, Antony; Gantet, Pascal; Laplaze, Laurent; Guyomarc'h, Soazig
Abstract: Lateral root organogenesis is a key process in the development of a plant's root system and its adaptation to the environment. During lateral root formation, an early phase of cell proliferation first produces a four-cell-layered primordium, and only from this stage onwards is a root meristem-like structure, expressing root stem cell niche marker genes, being established in the developing organ. Previous studies reported that the gene regulatory network controlling lateral root formation is organized into two subnetworks whose mutual inhibition may contribute to organ patterning. PUCHI encodes an AP2/ERF transcription factor expressed early during lateral root primordium development and required for correct lateral root formation. To dissect the molecular events occurring during this early phase, we generated time-series transcriptomic datasets profiling lateral root development in puchi-1 mutants and wild types. Transcriptomic and reporter analyses revealed that meristem-related genes were expressed ectopically at early stages of lateral root formation in puchi-1 mutants. We conclude that, consistent with the inhibition of genetic modules contributing to lateral root development, PUCHI represses ectopic establishment of meristematic cell identities at early stages of organ development. These findings shed light on gene network properties that orchestrate correct timing and patterning during lateral root formation. Abstract : Consistent with the hypothesis that mutual inhibition between gene regulatory subnetworks contributes to lateral root formation, we show that PUCHI represses early meristematic gene expression in developing root primordia.